A two-wheeled inverted pendulum robot with friction compensation. (September 2015) - Dai, Fuquan; Gao, Xueshan; Jiang, Shigong; Guo, Wenzeng; Liu, Yubai
Abstract: This paper introduces a method of design and implementation of a two-wheeled inverted pendulum (TWIP) robot with friction compensation. Friction in the drive mechanism is a critical factor of robot self-balancing and affects its performance. The friction parameters are identified based on the dynamic model of the drive mechanism. The dynamics of the whole robot system are obtained by the Lagrangian function method and take the robot drive mechanism friction into account. Sliding mode controllers for self-balancing and yaw motion are designed independently, although the TWIP robot is coupled as a nonlinear system. A low cost but low accuracy gyro and accelerator in consumer electronics grade is adopted to estimate the pitch angle and pitch rate. Using the sensor data from the gyro and accelerator fused with the help of a Kalman filter, the robot body pitch angle is obtained precisely, and these are the key state variables for TWIP control. The effect on the sensor installation location is analysed and corrected with innovation, and the precision of the pose estimation is improved accordingly. Several physical experiments are conducted, and the results demonstrate that the proposed method is effective.